Iron Chelates Alleviate Iron Chlorosis in Soybean on High pH Soils. (1st July 2014) - Gamble, A. V.; Howe, J. A.; Delaney, D.; van Santen, E.; Yates, R.
Abstract : High pH soils frequently lead to iron deficiency chlorosis (IDC) in soybean [ Glycine max (L.) Merr.]. As a result, yields for soybean are often reduced. Studies in the north‐central United States have shown improvements in grain yield after applying Fe chelates on calcareous soils, but this practice has not been evaluated in a southern climate. Two sites within the Blackbelt region of Alabama were evaluated for response to Fe‐EDDHA, Fe‐Citrate, and FeSO4 for their effect on yield and chlorosis in 2010, 2011, and 2012. Treatments were applied in‐furrow at planting, as a foliar spray at the V3 growth stage, or as a split‐application. Remote sensing, relative chlorophyll meter readings, and visual chlorosis scores (VCS) were assessed as methods for identifying degree of Fe chlorosis. At the location where IDC was most pronounced, all treatments of Fe‐EDDHA were effective at reducing VCS ratings when applied in‐furrow at planting; however, chlorosis evaluation through remote sensing and relative chlorophyll readings was not able to detect improvements in chlorosis measured with VCS. Treatments of Fe‐EDDHA at 4.5 kg product ha −1 increased yield whether applied as an in‐furrow at planting treatment or as a split application at planting and at V3 growth stage as a foliar spray. Treatments of Fe‐Citrate and FeSO4 did not improve yield as applied in this study. Results suggest that Fe‐EDDHA can be used in southern climates as a strategy to overcome IDC yield limitations.